The Comparison between Spectral and Entropic Measures Following Fatigue in Erector Spinae Muscles - Saeed Talebian; Maryam Saba; Hossein Bagheri; Gholamreza Olyaei; Shiva Mousav (Shiraz University of Medical Sciences, 2016)
Background: Surface electromyography (sEMG) of muscles is a non-invasive tool that can be helpful in the assessment of muscle function and some motor control evaluations. A loss of force, known as muscle fatigue is accompanied by changes in muscle electrical activity. One of the most commonly used surface EMG parameters which reflects paraspinal muscle fatigue during different tasks and positions is median frequency. Although it is widely known that the electromyography power spectrum shifts to lower frequencies during fatiguing contraction, an opinion exists that the validity of spectral shifts in assessment of fatigue is questionable. Some researchers have examined whether other quantities derived from sEMG signals are better indicators for muscle fatigue. Following cyclic flexion/extension and consequence fatigue, variation in sEMG signals may be complex for study. The aim of this study was to determine which of the median frequency (MF) or entropic (ENTR) is more sensitive for measuring muscular fatigue in erector spinae muscles during cyclic flexion/extension. Methods: Surface electromyography of erector spine muscles was recorded in 25 healthy subjects during cyclic dynamic contractions. The experimental session consisted of two parts: measurement of Maximal Voluntary Contraction (MVC), and performing the fatigue test. All subjects performed rhythmic flexion/extension with 50% MVC loading against B-200 Isostation, about 4-6 minutes. The MF and ENTR of the muscle activities were computed to assess muscular fatigue. Results: Paired sample t-tests showed that MF and ENTR changes after fatigue test were significant (P<0.001). Percentage changes of both MF and ENTR were reduced, this reduction for ENTR was more than 40% (P<0.001). Conclusion: It seems that the changes of ENTR in muscle activities have the ability to measure muscular fatigue and is more sensitive in comparison to MF.